Analisis Good Corporate Governance pada Kinerja Keuangan Bank Umum Syariah yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2020 - Nova Destiana; Andang Sunarto; Adi Setiawan (Al Maal: Journal of Islamic Economics and Banking, 2022)
The purpose of this study was to determine whether the board of commissioners, board of directors and audit committee have an effect on financial performance as measured by using ROA. This type of research is quantitative descriptive. The data used in this study are Islamic commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The analysis technique used is panel data regression with the help of Eviews 10. The results of this study partially show that the board of commissioners and the audit committee have no effect on financial performance, while the board of directors has an influence on financial performance. Meanwhile, simultaneously the three variables, namely the board of commissioners, the board of directors and the audit committee jointly affect the financial performance of Islamic commercial banks listed on the Indonesian Stock Exchange (IDX).